Formulation and Antioxidant Activity Analysis of Jotang Herb (Acmella paniculata) Extract Mask Cream - Kholifah, Eva; Fitriani, Via; Shobah, Afifah Nur (Universitas Muhammadiyah Yogyakarta, 2024)
Pollution in the environment can increase the production of reactive oxygen species (ROS), which can reduce the amount of antioxidants in the skin. Antioxidants are compounds that can inhibit oxidation reactions by binding to free radicals and reactive molecules. Herbaceous plant jotang (Acmella paniculata) has secondary metabolites such as flavonoids, alkaloids, tannins, and saponins, which can protect the internal and external organs of the body's cells from damage caused by free radicals on the skin. One of the treatment preparations used for the skin is a cream mask, as the use or application at the final level of skin care can improve cleanliness and health and stimulate and repair skin cells. This study aims to determine a formula that has a good antioxidant value using the DPPH method (2,2-diphenyl-1-pikrilhidrazyl). In this study, preparations were made with 3 formulas, namely Formula I (1% w/w), Formula II (10%w/w), and Formula 0 (Control). Evaluation of physical properties included organoleptic tests, homogeneity tests, spreadability tests, pH tests, viscosity tests, cream-type tests, and antioxidant tests. The result showed that the organoleptic test had a cream mask dosage in the form of semi-solid, distinctive jotang odor, light and dark green, had a homogeneous dosage form, spreadability around 5.1-5.7 with an average pH value of 6, had a good viscosity value and had a type of cream M/A and a high antioxidant value in formula II (10% w/w ) with an IC50 value of 21.959 μg/ml. Based on statistical tests, significant results were obtained of 0.000p (0.05) so that it can be interpreted that there was a significant difference in each concentration of jotang herb extract to the resulting IC50 value.